A large 4.5-year-old urethral meatus calculus with partial phimosis without urinary retention: A case report (Indian Journal of Case Reports, 2025)
In the lower urinary tract, calculi are usually observed in the bladder, prostate, and urethral locations. Here, we present the case of a 40-year-old laborer male patient who presented with complaints of dribbling of urine off and on, suprapubic pain for 1 week, and feeling of stone at the meatus for 4.5 years. X-ray of the pelvis was suggestive of a long slender stone near the urethral meatus. Kidney ureter and bladder ultrasonography suggest no upper tract changes and a large capacity bladder with increased post-void residual. The patient was managed surgically under spinal anesthesia. A meatotomy was done. About 1 cm incision was placed over the ventral aspect extending up to the stone and the stone delivered easily with proximal squeezing. The size of the stone was 2.7 cm × 0.9 cm. Catheter removal was done after 14 days. Large urethral meatus stone is not a common entity and long-time obstructed stone may lead to several complications such as upper tract damage, chronic renal failure, urinary bladder changes, severe urosepsis, and Fournier’s gangrene.